1999
DOI: 10.1086/313197
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared and Ultraviolet Spectrophotometry of Symbiotic Novae

Abstract: In this paper we present an atlas of near-infrared spectrophotometry of symbiotic novae and report results from nearly contemporaneous IUE observations. The data cover RT Ser, AG Peg, V1016 Cyg, V1329 Cyg, HM Sge, and Pu Vul, most of the known symbiotic novae that are observable from the northern hemisphere. Emission-line strengths for both spectral regions are tabulated. Extinction values are derived from He II j1640 in the UV and He II j10124 in the infrared. Spectral types are determined for the cool giant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…4, so this may be consistent. The same feature is also seen in the symbiotic nova PU Vul by Rudy et al (1999) and again identified as Fe II λλ 9176-9205.…”
Section: The λ 9220å Featuresupporting
confidence: 62%
“…4, so this may be consistent. The same feature is also seen in the symbiotic nova PU Vul by Rudy et al (1999) and again identified as Fe II λλ 9176-9205.…”
Section: The λ 9220å Featuresupporting
confidence: 62%
“…In these systems, despite the much smaller outburst amplitudes compared to those observed in novae, the total energy associated with the outburst may significantly exceed that of a classical nova. Currently very little is known about the line-emitting regions associated with the outburst of a symbiotic nova because of the long timescales to reach the maximum and the very much slower decays (Rudy et al, 1999). Symbiotics also fall in the category of the supersoft X-ray sources (Greiner, 1996) making them potential SN Ia progenitors (Hachisu et al, 1999).…”
Section: Symbiotic Starsmentioning
confidence: 99%
“…In these systems, despite the much smaller outburst amplitudes compared to those observed in novae, the total energy associated with the outburst may significantly exceed that of a classical nova. Currently very little is known about the line-emitting regions associated with the outburst of a symbiotic nova because of the long timescales to reach the maximum and the very much slower decays (Rudy et al, 1999). Symbiotics also fall in the category of the supersoft X-ray sources (Greiner, 1996) making them potential SN Ia progenitors (Hachisu et al, 1999).…”
Section: Symbiotic Starsmentioning
confidence: 99%